Account-Based Marketing and Sales : How to Improve Lead Generation and Sell More by Targeting the Companies That Will Grow Your Business. - Golec, Chris (John Wiley & Sons, Incorporated, 2019)
Account-Based Marketing is changing the discipline of marketing--Why? Business-to-business (B2B) companies spend $40 Billion on marketing each year, and they embrace tech-driven innovations, yet the traditional model for lead generation has not changed for decades. Why? In addition to the techniques being outdated, they create friction and distrust between marketing and sales teams. ABM has quickly gained traction with leading B2B companies because it aligns sales and marketing teams around the accounts that will have the most business impact. Instead of chasing a large volume of lower-quality, generic leads, ABM helps sales and marketing professionals coordinate their efforts against a specific set of target accounts. Despite the clear advantages of ABM, there continues to be much confusion around just how to implement it. Written by the leaders behind the successful marketing firm Demandbase, Account-Based Marketing explains how to execute a world-class ABM strategy from start to finish. Find out exactly how highly successful B2B companies are using Account-Based Marketing to grow their customer base Develop an effective strategy to adapt ABM principles for your own organization with its own unique needs Integrate your sales and marketing processes into an efficient, cohesive workflow Locate and attract the ideal clients for your business to increase revenue and open up new opportunities From building the right target account list and understanding the impact of ABM on marketing programs, to selling ABM within an organization and finding budget for the strategy, you'll find it all in this authoritative guide.